A method for preparing a MoO3@CuO / CF foam-based catalyst for photoelectrocatalytic nitrogen fixation.

CN116555782BActive Publication Date: 2026-10-20WUHAN TEXTILE UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310554858.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-17
Publication Date
2026-10-20
Estimated Expiration
2043-05-17

AI Technical Summary

Benefits of technology

(1)本发明直接使用三维多孔泡沫铜为催化剂载体,并在泡沫铜金属上原位生长出CuO纳米线,可以显著提高电极材料的电子导电性,增加电极材料的比表面积,提高电极材料的电容。泡沫铜的高孔隙率和大比表面积也为电催化反应和质量输送提供了较大的活性表面,暴露更多的活性位点,具有更强的光电性能。 同时泡沫铜为基体材料也避免了粉末催化剂需要涂附在基底上的复杂性操作,也避免了因涂附结合力不强,导致存在稳定性差的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116555782B_ABST
    Figure CN116555782B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of MoO3@CuO / CF foam-based catalyst, and studies application of the MoO3@CuO / CF foam-based catalyst in photoelectrocatalytic nitrogen fixation. The main process is as follows: taking ammonium heptamolybdate tetrahydrate as a molybdenum source and taking thioperoxide as a sulfur source, molybdenum disulfide nanospheres are prepared by using a hydrothermal method; copper hydroxide is obtained by immersing copper foam in a sodium hydroxide and ammonium persulfate solution; the obtained molybdenum disulfide is dispersed in ethanol, and then MoS2@Cu(OH)2 / CF precursors are obtained by coating; and the MoS2@Cu(OH)2 / CF precursors are calcined in a tube furnace under an air atmosphere to obtain MoO3@CuO / CF foam-based catalysts. The prepared catalysts have a three-dimensional structure, expose abundant active sites, and have better photoelectrocatalytic performance; and the prepared catalysts can be directly used as working electrodes to complete photoelectrocatalytic synthesis of ammonia under the action of a bias voltage and a xenon lamp irradiation. The method is simple in operation and low in cost, and the catalyst is easy to recycle and reuse. The catalyst is used for photoelectrocatalytic nitrogen fixation under normal temperature and pressure, and has excellent ammonia production activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention specifically relates to the preparation of a MoO3@CuO / CF foam-based catalyst and its application in photoelectrocatalytic nitrogen fixation, belonging to the field of photoelectrocatalytic materials technology. Background Technology

[0002] With societal development and the increasing use of fossil fuels, energy depletion is becoming a growing problem. Ammonia (NH3) is important in industry and agriculture as a chemical feedstock and a clean energy carrier. Although nitrogen makes up approximately 78% of the air, humans cannot directly utilize it. Ammonia is the most important nitrogen-containing compound, used to manufacture many key compounds and is a vital component of the global economy. Considering the greenhouse effect and other issues, there is growing interest in carbon-free, high-hydrogen ammonia nitrogen as a clean fuel carrier. Currently, nitrogen fixation in industrial production uses the Haber-Bosch process, but this method requires high temperature, high pressure, and a large amount of energy, emitting significant amounts of greenhouse gases and exacerbating global energy consumption and the greenhouse effect. Therefore, finding a sustainable and cost-effective ammonia production strategy to replace the Haber-Bosch process is crucial.

[0003] In natural environments, it has been discovered that rhizobia contain nitrogenase, which can selectively break nonpolar triple bonds, enabling nitrogen fixation under ambient temperature and pressure. Simultaneously, high-energy nitrogen fixation reactions can occur under the influence of lightning. Inspired by these natural processes, it is widely believed that the combined effects of photochemistry and electrochemistry can utilize the abundant nitrogen sources in the atmosphere for nitrogen fixation. Nitrogen fixation reactions using sunlight and low voltage under ambient temperature and pressure can reduce energy consumption and carbon dioxide emissions, effectively alleviating the problems associated with the HB process for ammonia production in current industrial nitrogen fixation. Photocatalytic nitrogen fixation experiments can be traced back to the 1980s, when Schrauzer and Guth discovered that titanium dioxide, under photocatalytic conditions, could reduce nitrogen and water to ammonia. Since then, various photocatalysts have been widely used in nitrogen fixation, such as TiO2, ZnO, CdS, MOFs, and black phosphorus. In the field of electrocatalytic nitrogen fixation, various noble metals such as Au, Ru, Pt, and Ag have been widely used. However, both photocatalysis and electrocatalysis have their own drawbacks. Photocatalytic nitrogen fixation mainly involves sunlight irradiating the catalyst to generate electron-hole pairs, thus initiating a redox reaction. However, the high recombination rate of photogenerated carriers and low light utilization hinder the occurrence of the photocatalytic nitrogen fixation reaction, resulting in low ammonia production efficiency. In electrocatalytic nitrogen fixation, the use of noble metal catalysts not only leads to high production costs but also requires consideration of the high energy barriers of nitrogen activation and hydrogen evolution reactions. The activity and selectivity of this process are often unsatisfactory, resulting in low Faradaic efficiency. Combining the advantages of photocatalysis and electrocatalysis, photoelectrocatalytic nitrogen fixation represents another promising nitrogen fixation method that can solve problems such as high surface recombination rates of photogenerated electrons and holes, oxidation of reaction products, and difficulties in catalyst recovery. Related studies have found that the ammonia nitrogen yield and Faradaic efficiency of the two-cell reaction system are both higher than those of the single-cell reaction system.

[0004] Current research on molybdenum-based materials has yielded various NRR catalysts, including Mo2C, MoS2, MoO2, and MoO3. MoO3 has shown excellent activity in both photocatalysis and electrocatalysis for nitrogen fixation. Wu et al. achieved plasma-driven photocatalytic N2 fixation using semiconductor plasma MoO3-x nanosheets. Zhao et al. proposed a nanofiber composite material formed by combining MoO3 and SnS2, exhibiting good photoelectric nitrogen fixation performance. Copper foam (CF) is an ideal material for manufacturing electrical equipment due to its excellent ductility, corrosion resistance, and impressive electrical conductivity. Cu-based oxides, due to their flexibility and similar oxidation states (Cu... + Cu 2+ and Cu 3+Due to their semiconductor properties, both MoO3 and CuO have been widely studied and applied in various fields such as biosensing, battery anode materials, photocatalysts, and electrocatalysts. Since both MoO3 and CuO are semiconductor materials, and each has been studied in photocatalytic and electrocatalytic nitrogen fixation, combining MoO3 with CuO to form a heterojunction composite catalyst, and using it as the working electrode material for photoelectrocatalysis, may have a synergistic effect on photoelectrocatalysis and could be applied in the field of photoelectrocatalytic nitrogen fixation. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing MoO3@CuO / CF foam-based materials and their application in the field of photoelectrocatalytic nitrogen fixation. This invention applies it to the highly efficient and selective photoelectrocatalysis of nitrogen, and utilizes a dual-cell photoelectrocatalytic reaction system to achieve spatial separation of redox reactions, combining photocatalysis and electrocatalysis to enhance the synthesis efficiency and Faraday efficiency of ammonia nitrogen.

[0006] To achieve the above objectives, the technical solution adopted by the present invention for preparing a MoO3@CuO / CF foam-based material is as follows:

[0007] (1) Preparation of molybdenum disulfide nanospheres: 3 mmol of ammonium heptamolybdate tetrahydrate (NH4)6Mo7O 24 • Dissolve 4H₂O and 8 mmol thiourea in 30 mL of deionized water. Transfer the solution to a high-pressure reactor (70 mL) and maintain at 200 °C for 24 hours. After cooling, collect the product, wash 3–5 times with deionized water and anhydrous ethanol, and then vacuum dry overnight at 60 °C.

[0008] (2) Preparation of Cu(OH)2 / CF foam-based material: Cut the copper foam into pieces with a size of 1×2 cm 2 The copper foam was washed several times with 3 mol / L hydrochloric acid, ethanol, and deionized water, and then dried at room temperature. 3.2 g of sodium hydroxide was dissolved in 22 ml of deionized water, and 0.89 g of ammonium persulfate was dissolved in 8 ml of deionized water. The two solutions were then mixed thoroughly. The treated copper foam was immersed in the mixed solution and stirred for 30 minutes. It was then washed several times with deionized water and anhydrous ethanol, and then dried under vacuum at 60 °C overnight.

[0009] (3) Preparation of MoO3@CuO / CF foam-based material: A certain amount of molybdenum disulfide was ultrasonically dispersed in anhydrous ethanol and coated onto a 1×2 cm layer. 2 MoS2@Cu(OH)2 / CF precursor was obtained by vacuum drying at 60 °C overnight on Cu(OH)2 / CF stereomaterial. The precursor was then placed in a tube furnace and calcined in air atmosphere. After natural cooling, MoO3@CuO / CF three-dimensional material was obtained.

[0010] Specifically: In step (3), the amount of molybdenum disulfide is 0.5~2 mg, and the amount of ethanol is 0.5~2 mL, with a ratio of 1:1. The ultrasonic stirring time after adding molybdenum disulfide is 60 minutes. The precursor is calcined in a tube furnace at a temperature of 150~300 ℃ for 120~180 minutes, with a heating rate of 5 ℃ / min.

[0011] The above method was used to prepare MoO3@CuO / CF foam-based material.

[0012] The above-mentioned MoO3@CuO / CF foam-based material is used in photoelectrochemical nitrogen fixation.

[0013] Specifically, a three-electrode system was employed, with a two-cell reactor. The cathode and anode chambers were separated by a Nafion membrane. Ag / AgCl was used as the reference electrode, a Pt sheet as the counter electrode, a foam-based catalyst as the working electrode, a 300 W xenon lamp as the light source, and 80 mL of 0.1 M Na₂SO₄ solution as the electrolyte solution. All potentials measured in the current operation were calibrated to RHE using the Nernst equation: E RHE = E Ag / AgCl + 0.197 + 0.059 pH.

[0014] Before the nitrogen fixation reaction, N2 is introduced into the anode and cathode electrolytes at a flow rate of 100 sccm for 30 min to remove dissolved oxygen in the water. During the nitrogen fixation reaction, N2 is continuously introduced at a flow rate of 50-80 sccm while maintaining room temperature. A 300W xenon lamp is turned on and a bias voltage is applied to carry out the photoelectrocatalytic synthesis of ammonia.

[0015] The ammonia nitrogen detection methods used in the experiment were salicylic acid spectrophotometry and phenolic salt spectrophotometry.

[0016] In this invention, the consumables, reagents, instruments, etc. listed are all conventional equipment.

[0017] In this invention, "room temperature" refers to the normal ambient temperature, which can be 15 to 30 °C.

[0018] The advantages of this invention are: (1) This invention directly uses three-dimensional porous copper foam as a catalyst support and grows CuO nanowires in situ on the copper foam metal, which can significantly improve the electronic conductivity of the electrode material, increase the specific surface area of ​​the electrode material, and improve the capacitance of the electrode material. The high porosity and large specific surface area of ​​copper foam also provide a large active surface for electrocatalytic reaction and mass transport, exposing more active sites and exhibiting stronger photoelectric properties. At the same time, using copper foam as the matrix material avoids the complex operation of coating powder catalysts onto a substrate, and also avoids the problem of poor stability caused by weak coating adhesion.

[0019] (2) Under the synergistic effect of MoO3 and CuO, the present invention enhances the range of light utilization and combines photocatalysis and electrocatalysis. By using a dual-cell reaction system and applying an appropriate voltage, electrons and holes are directionally separated, reducing carrier recombination. Oxidation and reduction reactions are spatially separated, inhibiting the oxidation of ammonia nitrogen, achieving selective synthesis of ammonia nitrogen, suppressing the generation of by-products and the occurrence of hydrogen evolution reaction, thereby significantly improving the yield of ammonia nitrogen and the photoelectric utilization efficiency.

[0020] (3) This invention tested the photoelectrocatalytic nitrogen fixation performance of MoO3@CuO / CF three-dimensional materials with different MoO3 content ratios at multiple voltages, and determined the nitrogen fixation performance, Faraday efficiency, and voltage value of the optimal ratio. Its performance is about 1.8 times higher than that of pure CuO / CF without MoO3 composite, and it also shows a certain improvement in photocatalytic and electrocatalytic nitrogen fixation performance compared with the reported copper oxide-based photocatalysis. At the same time, the composite catalyst has strong stability, can be reused, and is simple and readily available. Attached Figure Description

[0021] Figure 1 This is a scanning electron microscope image of the MoO3@CuO / CF three-dimensional material obtained in Example 2 of the present invention.

[0022] Figure 2 The images show the XRD patterns of MoO3@CuO / CF and MoO3 in Examples 1-7 of this invention.

[0023] Figure 3 This is a schematic diagram of the H-type dual-pool reactor system and reaction principle of the present invention.

[0024] Figure 4 This is a standard curve of ammonia nitrogen measured using the salicylic acid method in this invention.

[0025] Figure 5 This is a standard curve diagram of the ammonia nitrogen phenol salt method measured in this invention.

[0026] Figure 6The graphs show the photoelectrochemical nitrogen fixation performance and Faraday efficiency of the MoO3@CuO / CF (MoCu-1, MoCu-2, MoCu-3, MoCu-4) and CuO / CF materials prepared in Examples 1, 2, 3, and 4 at preset potentials.

[0027] Figure 7 The graphs show the photoelectrocatalytic nitrogen fixation performance and Faraday efficiency of the MoO3@CuO / CF material prepared in Example 2 at different potentials.

[0028] Figure 8 The graph shows a comparison of the photoelectrocatalytic nitrogen fixation cycle performance of the MoO3@CuO / CF material prepared in Example 2 at a preset potential.

[0029] Figure 9 The graph shows a comparison of the nitrogen fixation and ammonia production effects of the MoO3@CuO / CF material prepared in Example 2 with other typical MoO3-based semiconductor composite materials.

[0030] Figure 10 UV-Vis diffuse reflectance spectra of molybdenum trioxide fibers, MoO3@CuO / CF three-dimensional materials, and CuO / CF obtained in Example 2.

[0031] Figure 11 Linear scanning voltammetry diagram of the MoO3@CuO / CF material obtained in Example 2. Implementation

[0032] The invention will be further explained below with reference to specific examples and accompanying drawings.

[0033] Example 1 (1) Preparation of molybdenum disulfide nanospheres: 3 mmol of ammonium heptamolybdate tetrahydrate (NH4)6Mo7O 24 • Dissolve 4H₂O and 8 mmol thiourea in 30 mL of deionized water. Transfer the solution to a high-pressure reactor (70 mL) and place it in a forced-air drying oven at 200 °C for 24 hours. After cooling, collect the product by vacuum filtration, wash 3–5 times with deionized water and anhydrous ethanol, and then vacuum dry overnight at 60 °C to obtain the final product.

[0034] (2) Preparation of Cu(OH)2 / CF foam-based material: Cut the copper foam into pieces with a size of 1×2 cm 2 The sample was washed several times with 3 mol / L hydrochloric acid, ethanol, and deionized water, and then dried at room temperature. 3.2 g of sodium hydroxide was dissolved in 22 ml of deionized water, and 0.89 g of ammonium persulfate was dissolved in 8 ml of deionized water. The two solutions were then mixed thoroughly. The treated foam was then immersed in the mixed solution and stirred for 30 minutes. The sample was washed several times with deionized water and anhydrous ethanol, and then dried under vacuum at 60 °C overnight.

[0035] (3) Preparation of MoO3@CuO / CF foam-based material: 1 mg of molybdenum disulfide was weighed and dispersed in 1 mL of anhydrous ethanol. After ultrasonic stirring for 60 minutes, it was coated onto a 1×2 cm foam substrate. 2 MoS2@Cu(OH)2 / CF precursor was obtained by vacuum drying at 60 °C overnight on Cu(OH)2 / CF stereomaterial. The precursor was then placed in a tube furnace and calcined at 250 °C for 150 minutes in air atmosphere at a heating rate of 5 °C / min. After natural cooling, MoO3@CuO / CF foam-based material was obtained, denoted as MoCu-1.

[0036] MoCu-1 was characterized using XRD, such as... Figure 2 As shown in (MoCu-1).

[0037] Example 2 (1) The preparation of molybdenum disulfide is the same as in Example 1.

[0038] (2) The preparation of Cu(OH)2 / CF is the same as in Example 1.

[0039] (3) The preparation process of MoO3@CuO / CF is the same as in Example 1, except that the amount of molybdenum disulfide is 2 mg and the amount of ethanol is 2 ml. The resulting MoO3@CuO / CF foam-based material is denoted as MoCu-2.

[0040] MoCu-2 was characterized using scanning electron microscopy, such as... Figure 1 As shown, the MoO3@CuO / CF foam-based material consists of MoO3 nanospheres grown on CuO nanofibers.

[0041] MoCu-3 was characterized using XRD, such as... Figure 2 As shown in (MoCu-2).

[0042] Example 3 (1) The preparation of molybdenum disulfide is the same as in Example 1.

[0043] (2) The preparation of Cu(OH)2 / CF is the same as in Example 1.

[0044] (3) The preparation process of MoO3@CuO / CF is the same as in Example 1, except that the amount of molybdenum disulfide is 3 mg and the amount of ethanol is 3 ml. The resulting MoO3@CuO / CF foam-based material is denoted as MoCu-3.

[0045] MoCu-3 was characterized using XRD, such as... Figure 2 As shown in (MoCu-3).

[0046] Example 4 (1) The preparation of molybdenum disulfide is the same as in Example 1.

[0047] (2) The preparation of Cu(OH)2 / CF is the same as in Example 1.

[0048] (3) The preparation process of MoO3@CuO / CF is the same as in Example 1, except that the amount of molybdenum disulfide is 4 mg and the amount of ethanol is 4 ml. The resulting MoO3@CuO / CF foam-based material is denoted as MoCu-4.

[0049] MoCu-4 was characterized using XRD, such as... Figure 2 As shown in (MoCu-4).

[0050] Example 5 (1) The preparation of molybdenum disulfide is the same as in Example 1.

[0051] (2) The preparation of Cu(OH)2 / CF is the same as in Example 1.

[0052] (3) The preparation process of MoO3@CuO / CF is the same as in Example 1, except that the amount of molybdenum disulfide is 2 mg and the amount of ethanol is 2 ml. Calcination in a tube furnace is stabilized at 150 °C for 180 minutes. The resulting MoO3@CuO / CF foam-based material is denoted as MoCu-5.

[0053] MoCu-5 was characterized using XRD, such as... Figure 2 As shown in (MoCu-5).

[0054] Example 6 (1) The preparation of molybdenum disulfide is the same as in Example 1.

[0055] (2) The preparation of Cu(OH)2 / CF is the same as in Example 1.

[0056] (3) The preparation process of MoO3@CuO / CF is the same as in Example 1, except that the amount of molybdenum disulfide is 3 mg and the amount of ethanol is 3 ml. Calcination in a tube furnace is stabilized at 200 °C for 120 minutes. The resulting MoO3@CuO / CF foam-based material is denoted as MoCu-6.

[0057] MoCu-6 was characterized using XRD, such as... Figure 2 As shown in (MoCu-6).

[0058] Example 7 (1) The preparation of molybdenum disulfide is the same as in Example 1.

[0059] (2) The preparation of Cu(OH)2 / CF is the same as in Example 1.

[0060] (3) The preparation process of MoO3@CuO / CF is the same as in Example 1, except that the amount of molybdenum disulfide is 3 mg and the amount of ethanol is 3 ml. Calcination in a tube furnace is stabilized at 300 °C for 180 minutes. The resulting MoO3@CuO / CF foam-based material is denoted as MoCu-7.

[0061] MoCu-7 was characterized using XRD, such as... Figure 2 As shown in (MoCu-7).

[0062] For comparison, pure CuO / CF was prepared using a method referenced from relevant papers, specifically: copper foam was cut into pieces measuring 1×2 cm. 2 The material was washed several times with 3 mol / L hydrochloric acid, ethanol, and deionized water, and then dried at room temperature. 3.2 g of sodium hydroxide was dissolved in 22 ml of deionized water, and 0.89 g of ammonium persulfate was dissolved in 8 ml of deionized water. The two solutions were then mixed thoroughly. The treated foam was soaked and stirred in the mixed solution for 30 minutes. The foam was washed several times with deionized water and anhydrous ethanol, and then vacuum dried overnight at 60 °C to obtain Cu(OH)₂ / CF. The Cu(OH)₂ / CF was then placed in a tube furnace and calcined at 250 °C for 180 minutes in air atmosphere. After natural cooling, CuO / CF material was obtained. XRD characterization was performed, as shown in the figure. Figure 2 The preparation shown yielded pure MoO3 powder. The method referenced relevant papers, specifically: 3 mmol of ammonium heptamolybdate tetrahydrate (NH4)6Mo7O was used. 24 4H₂O and 8 mmol thiourea were dissolved in 30 mL of deionized water; the solution was transferred to a high-pressure reactor (70 mL) and placed in a forced-air drying oven at 200 °C for 24 hours; after cooling, the product was collected by vacuum filtration, washed 3-5 times with deionized water and anhydrous ethanol, and then vacuum dried overnight at 60 °C to obtain MoS₂ nanospheres. The MoS₂ nanospheres were then calcined at 250 °C for 150 minutes in air at a heating rate of 5 °C / min. After natural cooling, MoO₃ powder was obtained. XRD characterization was performed, as shown below. Figure 2 As shown.

[0063] Application of MoO3@CuO / CF foam-based materials in photoelectrocatalytic nitrogen fixation.

[0064] MoO3@CuO / CF and CuO / CF samples from Examples 1, 2, 3, and 4 were selected for photoelectrochemical nitrogen fixation performance experiments.

[0065] The photoelectrochemical nitrogen fixation experiment specifically employed a three-electrode system. The reactor was a two-cell reaction system, with a Nafion membrane separating the cathode and anode chambers. Ag / AgCl was used as the reference electrode, a Pt sheet as the counter electrode, and foam-based material directly as the working electrode. A 300 W xenon lamp was used as the light source, and 0.1 M Na₂SO₄ solution was used as the electrolyte solution. All potentials measured during the experiment were calibrated to RHE using the Nernst equation: E RHE = E Ag / AgCl + 0.197 + 0.059 pH. The reaction apparatus system and principle are as follows: Figure 3 As shown.

[0066] Pretreatment of Nafion membranes: First, heat in 5% H2O2 at 80 ℃ for 1 h, then remove and rinse thoroughly with deionized water. Then heat in 80 ℃ water for 1 h, followed by heating in 0.5 M H2SO4 solution at 80 ℃ for 1 h, and finally heating in 80 ℃ water for 1 h, then rinsing with deionized water for later use.

[0067] The ammonia nitrogen detection methods used in the experiment were the salicylic acid spectrophotometric method and the phenolate spectrophotometric method. The salicylic acid method followed the People's Republic of China National Environmental Protection Standard HJ 536-2009, and the phenolate method followed the People's Republic of China National Standard GB / T5750.5-2006. The standard curve was plotted as follows... Figure 4 As shown, the standard curve for the salicylic acid method is as follows: Figure 5 As shown, the standard curve for the phenolate method.

[0068] Before the nitrogen fixation reaction, high-purity N2 was introduced into the anolyte and cathode electrolytes at a flow rate of 100 sccm for 30 min to remove dissolved oxygen. During the nitrogen fixation reaction, N2 was continuously introduced at a flow rate of 50–80 sccm while maintaining room temperature. A 300 W xenon lamp was turned on, and a bias voltage (-0.5 to -1.0 V) was applied to carry out the photoelectrocatalytic synthesis of ammonia. Its nitrogen fixation performance is as follows: Figure 6 As shown, MoCu-2 exhibits the best photoelectrochemical nitrogen fixation effect, such as... Figure 7 As shown, under illumination and a voltage of -0.7 V, the highest nitrogen fixation efficiency was observed, approximately 10.2 μmol·h⁻¹. -1 ·cm -2 At a voltage of -0.7V, it exhibits the highest faradaic efficiency of approximately 10.5%, which is an improvement over pure CuO / CF in both photoelectrocatalytic nitrogen fixation performance and faradaic efficiency.

[0069] This invention also investigated the nitrogen fixation stability of the MoO3@CuO / CF foam-based material (MoCu-2) of Example 2, such as... Figure 8 As shown, it still has excellent nitrogen fixation effect after four cycles.

[0070] This invention also compares the nitrogen fixation and ammonia production effects of the catalyst (MoCu-2) with those of the previously published invention patent (SnMo-3, application number 202211169901.4), such as... Figure 9 As shown, MoCu-2 exhibits superior performance in nitrogen fixation and ammonia production efficiency, with a nearly three-fold improvement, which can be attributed to the supporting effect of the copper foam substrate. SnMo-3 has advantages in terms of low cost, availability, and stability.

[0071] To investigate the photocatalytic performance of the material, the MoO3@CuO / CF foam-based material (MoCu-2) from Example 2 was selected for UV-Vis diffuse reflectance spectroscopy testing, as shown below. Figure 10 As shown, MoO3 mainly absorbs ultraviolet light and has a weak absorption capacity for visible light, with an absorption edge of about 420 nm. MoCu-2 has a significantly larger light absorption range than pure MoO3. Therefore, the combination of MoO3 and CuO enhances its absorption of visible and near-infrared light and improves its photocatalytic performance.

[0072] To investigate the electrocatalytic performance of the material, the MoO3@CuO / CF foam-based material (MoCu-2) from Example 2 was selected for linear sweep voltammetry testing, as shown below. Figure 11 As shown; the specific experimental parameters were: initial potential of 0.0 V; termination potential of -1.2 V; scan rate of 0.01 V / s; sampling interval of 0.001 V; nitrogen and argon atmospheres were selected, and gas was continuously introduced into the H-type double-cell reactor at a gas flow rate of 50 mL / min for 30 min; the experiment showed that the current density of the material was significantly greater under nitrogen atmosphere than under argon atmosphere, proving that the material has certain electrocatalytic nitrogen fixation performance.

[0073] It should be noted that the above-described technical content of the present invention is only for explanation and clarification to enable those skilled in the art to understand the technical essence of the present invention, and therefore the described technical content is not intended to limit the scope of protection of the present invention; the scope of protection of the present invention shall be determined by the claims; those skilled in the art should know that any modifications, equivalent substitutions and improvements made based on the essential spirit of the present invention shall be within the scope of protection of the present invention.

Claims

1. A method for preparing a MoO3@CuO / CF foam-based catalyst, characterized in that, The steps for preparing the catalyst are as follows: (1) Preparation of molybdenum disulfide nanospheres: Specifically, 3 mmol of ammonium heptamolybdate tetrahydrate (NH4)6Mo7O 24 • Dissolve 4H₂O and 8 mmol of thiourea in 30 mL of deionized water. Transfer the solution to a 70 mL high-pressure reactor and maintain the temperature at 200 °C for 24 hours. After cooling, collect the product, wash it 3–5 times with deionized water and anhydrous ethanol, and then vacuum dry it overnight at 60 °C. (2) Preparation of Cu(OH)2 / CF foam-based material: Specifically, copper foam is cut into pieces with a size of 1×2 cm. 2 The copper foam was washed several times with hydrochloric acid, ethanol, and deionized water, and dried at room temperature. 3.2 g of sodium hydroxide was dissolved in 22 ml of deionized water, and 0.89 g of ammonium persulfate was dissolved in 8 ml of deionized water. The two solutions were then mixed thoroughly. The treated copper foam was immersed in the mixed solution and stirred for 30 minutes. It was then washed several times with deionized water and anhydrous ethanol, and finally dried under vacuum at 60 °C overnight. (3) Preparation of MoO3@CuO / CF foam-based catalyst: Specifically, a certain amount of molybdenum disulfide was ultrasonically stirred and dispersed in anhydrous ethanol, and then coated onto a 1×2 cm film. 2 MoS2@Cu(OH)2 / CF precursor was obtained by vacuum drying at 60 °C overnight on Cu(OH)2 / CF stereomaterial. The precursor was placed in a tube furnace and calcined in air atmosphere. After natural cooling, MoO3@CuO / CF foam-based material was obtained.

2. The preparation method of the MoO3@CuO / CF foam-based catalyst according to claim 1, characterized in that, In step (3), the amount of molybdenum disulfide is (1~4) mg, the amount of ethanol is 1~4 mL, the ratio is 1:1, the ultrasonic stirring time for adding molybdenum disulfide is 60 minutes, the temperature of the precursor calcined in the tube furnace is 150~300 ℃, the time is 120~180 minutes, and the heating rate is 5 ℃ / min.

3. The application of the MoO3@CuO / CF foam-based catalyst prepared by the method of claim 1 in photoelectrochemical nitrogen fixation.

4. The application according to claim 3, characterized in that, A three-electrode system was employed, with the reactor being an H-type two-cell reaction system. The cathode and anode chambers were separated by a Nafion membrane. Ag / AgCl was used as the reference electrode, a Pt sheet as the counter electrode, and a foam-based catalyst as the working electrode. A 300 W xenon lamp was used as the light source, and 0.1 M Na₂SO₄ solution was used as the electrolyte solution. All potentials measured during the operation were calibrated to RHE using the Nernst equation: E RHE = E Ag / AgCl + 0.197 + 0.059 pH.

5. The application according to claim 4, characterized in that: Before the nitrogen fixation reaction, N2 was introduced into the electrolyte at a flow rate of 100 sccm for 30 min to remove dissolved oxygen in the water. During the nitrogen fixation reaction, N2 was continuously introduced at a flow rate of 50-80 sccm while maintaining room temperature. A 300 W xenon lamp was turned on and a bias voltage was applied to carry out the photoelectrocatalytic synthesis of ammonia. The ammonia nitrogen was detected by salicylic acid spectrophotometry and indophenol salt spectrophotometry.

Citation Information

Patent Citations

  • Self-supporting heterostructure nanotube electrocatalytic material as well as preparation method and application thereof

    CN114457372A

  • Preparation method of photoelectrocatalytic nitrogen fixation SnS2atMoO3 fiber

    CN115613054A